Pengaruh Customer Relationship Management Terhadap Pembelian Ulang di Mediasi Kepercayaan Pelanggan Toko Ritel Makkiyah - Ahmad Faruqi Aziz; Adya Hermawati; Choirul Anam (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
In the highly competitive retail industry, companies must go beyond marketing. They must also prioritize strong customer relationships and trust. This study examines how Customer Relationship Management (CRM) influences repeat purchases at Makkiyah Retail Stores, with customer trust as the connecting factor. Using quantitative methods and explanatory approaches, the study collected data from 110 returning customers through a Likert-scale questionnaire. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The study findings indicate that CRM has a significant positive effect on repeat purchases, both directly and through increasing customer trust levels. Customer trust plays a significant role in strengthening the relationship between CRM and repeat purchase decisions. These findings highlight the importance of consistent, innovative, and trust-focused CRM management to enhance loyalty and repeat purchases in a competitive retail environment.